Website-Based Information System for Recording Sales and Purchase Activities at Rayyan's Grocery Store - Efendi, Tino Feri (Institut Teknologi Bisnis AAS Indonesia, 2024)
Toko Sembako Neena Solo is a grocery store business located in Surakarta, specializing in the sale of staple products such as rice, cooking oil, sugar, and eggs. The store conducts transactions by purchasing products from suppliers and reselling them to customers. However, the transaction records for both purchases and sales are still manually documented in a notebook, which poses risks such as the loss or damage of documents and makes it difficult for the store owner to perform financial calculations. Therefore, there is a need to develop a web-based information system to facilitate the recording of sales and purchase transactions, as well as to support the store’s financial report management. This information system is designed for three types of users: admin, store staff, and the store owner. The system development follows the waterfall method, which includes requirement analysis, system design, coding, testing, and system maintenance. System testing is conducted using the Black Box method. The result of this research is a web-based transaction recording system that helps store staff and owners manage transaction data and generate sales and purchase reports.